Cours particulier avec Paul B. Preciado (1/2) (2019)
« Féminin » ou « masculin » ? Dès la naissance, il faut choisir. Sur les papiers d’identité, les formulaires d’inscription, les bulletins d’adhésion, il y a toujours ces deux petites cases à cocher. Comme si le monde se divisait en deux catégories : les hommes et les femmes. C’est oublier que le genre est une fiction, un discours biopolitique. C’est oublier, aussi, que l’identité n’est jamais une essence mais une construction. D’où vient cette binarité du genre ? Pourquoi la citoyenneté n’est réservée qu’aux personnes cisgenres ? Comment déconstruire ce rapport normatif entre sexe, genre et reproduction ? Pour dépasser cette dichotomie de genre, Victoire Tuaillon reçoit Paul B. Preciado, philosophe, commissaire d’exposition et auteur dans un grand entretien en deux épisodes. La suite de ce cours particulier sera disponible dès le 9 mai 2019. RÉFÉRENCES CITÉES DANS L’ÉMISSION Retrouvez toutes les références et ressources de l'épisode à l'adresse https://www.binge.audio/podcast/les-c... CRÉDITS Les couilles sur la table est un podcast de Victoire Tuaillon produit par Binge Audio. Réalisation : Quentin Bresson. Stagiaire : Nadia Chapelle. Générique : Théo Boulenger. Identité graphique : Sébastien Brothier (Upian). Chargée de production : Juliette Livartowski. Chargée d’édition : Diane Jean. Direction des programmes : Joël Ronez. Direction de la rédaction : David Carzon. Direction générale : Gabrielle Boeri-Charles.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; philosophie; pol5480; premier cycle; ressource en ligne; sciences humaines; thématiques; transféminisme

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres